Human RPA phosphorylation by ATR stimulates DNA synthesis and prevents ssDNA accumulation during DNA-replication stress - Vassin, Vitaly M. (Company of Biologists, 2009)
ATR is an essential kinase activated in response to DNA-replication stress, with a known target being the RPA2 subunit of human replication protein A (RPA). We find that S33-RPA2 phosphorylation by ATR occurs primarily in the late-S and G2 phases, probably at sites of residual stalled DNA-replication forks, with S33-P-RPA2 contained within nuclear repair centers. Although cells in which endogenous RPA2 was `replaced' with an RPA2 protein with mutations T21A and S33A (T21A/S33A-RPA) had normal levels of DNA replication under non-stress conditions, the mutant cells were severely deficient in the amount of DNA synthesis occurring during replication stress. These cells also had abnormally high levels of chromatin-bound RPA, indicative of increased amounts of single-stranded DNA (ssDNA) and showed defective recovery from stress. Cells replaced with the mutant RPA2 also generated G1 cells with a broader DNA distribution and high levels of apoptosis following stress, compared with cells expressing wild-type RPA2. Surprisingly, cells expressing the wild-type RPA2 subunit had increased levels of stress-dependent DNA breaks. Our data demonstrate that RPA phosphorylation at the T21 and S33 sites facilitates adaptation of a DNA-replication fork to replication stress.